The boundary of smallholder producers’ cooperatives: A conceptual and empirical analysis - Tadesse, Getaw; Abate, Gashaw T.; Ergano, Kebebe (John Wiley & Sons, 2019)
In this study we explain the concepts, determinants and imperatives of boundary in smallholder producers’ cooperatives both conceptually and empirically. The conceptual framework indicates the importance of the type of goods (being a club good or not) and range of activities that a cooperative provides to its members in defining a competitive boundary. Using unique organisational and market level data from Ethiopia, we then test empirically whether the observed (weak) performance of producers’ cooperatives in Africa is explained by their organisational boundary – the type and range of goods or services they provide to members. The empirical results confirm that the competitiveness of producers’ cooperatives is significantly correlated with the type and number of services – i.e. cooperatives that provide club goods and a limited range of services are found to be more competitive. The results also suggest that a considerable number of cooperatives in Ethiopia engage in markets where they do not have competitive advantage. Overall, we demonstrate the importance of properly defining a viable boundary – proper selection of services (or markets) and limiting the range of services – for improving the competitiveness of membership‐based producer cooperatives in Africa.